New records of Aphids (Hemiptera: Aphidoidea) and their host-plants from northern Chile - Heie, O.E.=700 1 Petteráon, J.; Fuentes-Contreras, E.; Niemeyer, H.M.
(Es, En)
Ilus., 22 ref.
Keywords: HEMIPTERA; APHIDOIDEA; IDENTIFICACION; ESPECIES NUEVAS; REGISTRO; CHILE; REVISTA CHILENA DE ENTOMOLOGIA